Identifying and prioritizing the professional competencies of librarian’s Iranian public libraries - Mansoor Koohi Rostami; Donya Safaei; Abdul Hossein FarajPahlou (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2023)
Purpose: The purpose of this research is to identify and extract the professional competencies of the librarians of Iran’s public libraries, and to determine the importance of each of them in order to prioritize and rank them. Method: This research is an applied study employing a mixed research methodology. The study divided in two distinct stage. In the initial phase, a purposive selection of 61 Persian and English articles was analyzed using the meta-synthesis method. Then 104 codes were extracted using experts’ opinions, and the validity of these codes was confirmed through their content validity and their reliability was measured and confirmed with Cohen’s Kappa test. During the quantitative stage, each factor was ranked by distributing the questionnaire among 62 experts and using Shannon’s entropy method. Findings: This research reveals a pioneering exploration into the professional competencies of librarians in Iran’s public libraries, resulting in the identification of four crucial factors, 10 main components, and an extensive 72 sub-components that categorize these competencies. The ‘Ability’ factor, consisting of specialized ability and thinking ability, emerges as a cornerstone with conceptualizations across 9 sub-components. The ‘Feature’ factor, consisting of occupational and behavioral characteristics, was conceptualized by 19 sub-components. The ‘Skills’ factor, including managerial, social, occupational, and technological skills, was conceptualized by 32 sub-components. Lastly, the ‘Knowledge’ factor, comprising knowledge related to society and specialized knowledge, was conceptualized by 12 sub-components. Quantitative analysis, using the innovative Shannon entropy method, provides a nuanced understanding of the significance attached to each competency. The results of this analysis shows that ‘knowledge’ holds the highest weight (0/2575), establishing it as the most critical competency for librarians in Iran’s public libraries. Following closely, the ‘Skill’ factor secures the second position with a weight of 0/2545. ‘Ability’ and ‘Characteristics’ factors, with weights of 0.2498 and 0.2382, respectively, are ranked third and fourth. Originality/value: This research stands out in its original contribution to the field of library science by systematically identifying and prioritizing the professional competencies of librarians in Iran’s public libraries. The comprehensive validation process, including content validity and reliability assessments, ensures the robustness of the identified competencies. The emphasis on specialized ability, thinking ability, occupational and behavioral characteristics, managerial, social, occupational, and technological skills, as well as knowledge related to society and specialized knowledge, shows a nuanced understanding of the multifaceted nature of librarianship. In summary, this research breaks new ground in the systematic exploration, categorization, and prioritization of professional competencies, offering a valuable framework for improving the competencies of librarians in the unique context of Iranian public libraries. These findings not only contribute to the academic understanding of librarianship but also offer practical insights for enhancing the proficiency of librarians in this context. Furthermore, the nuanced categorization and prioritization presented in this research provide a valuable framework for the ongoing development of professional competencies and qualifications in this field.